Impact on cardiovascular disease events of the implementation of Argentina's national tobacco control law. Issue 2 (23rd October 2012) - Konfino, Jonatan; Ferrante, Daniel; Mejia, Raul; Coxson, Pamela; Moran, Andrew; Goldman, Lee; Pérez-Stable, Eliseo J
Abstract : Background: Argentina's congress passed a tobacco control law that would enforce 100% smoke-free environments for the entire country, strong and pictorial health warnings on tobacco products and a comprehensive advertising ban. However, the Executive Branch continues to review the law and it has not been fully implemented. Our objective was to project the potential impact of full implementation of this tobacco control legislation on cardiovascular disease. Methods: The Coronary Heart Disease (CHD) Policy Model was used to project future cardiovascular events. Data sources for the model included vital statistics, morbidity and mortality data, and tobacco use estimates from the National Risk Factor Survey. Estimated effectiveness of interventions was based on a literature review. Results were expressed as life-years, myocardial infarctions and strokes saved in an 8-year-period between 2012 and 2020. In addition we projected the incremental effectiveness on the same outcomes of a tobacco price increase not included in the law. Results: In the period 2012–2020, 7500 CHD deaths, 16 900 myocardial infarctions and 4300 strokes could be avoided with the full implementation and enforcement of this law. Annual per cent reduction would be 3% for CHD deaths, 3% for myocardial infarctions and 1% for stroke. If a tobacco price increase is implemented the projected avoided CHD deaths, myocardial infarctions and strokes would be 15 500, 34 600 and 11 900, respectively. Conclusions: Implementation of the tobacco control law would produce significant public health benefits in Argentina. Strong advocacy is needed at national and international levels to get this law implemented throughout Argentina.